(untitled) (Altre Modernità, 2015)
Despite their important role in forging, constructing and self-ascribing social identities and shaping popular culture, sports have long been a marginalized subject of social science inquiry, cultural studies, and research on international politics. Only in recent years this has begun to change. The article seeks to advance the still nascent but emerging cross-disciplinary field of research on sports and global politics in two ways: first, by addressing largely unexplored issues of sports, politics, and social conflicts, putting the spotlight on sociopolitical arenas beyond commercialized sports mega events, which have attracted most scholarly attention in contemporary research; and second, by generating hypotheses on the indirect political effects of sports cultures, in particular on the relationship between local social identities—reinforced through sports—and cosmopolitan value change. These interlinked spatial and substantive claims ground a new critical research framework and agenda: it examines sports as profoundly embedded in socioeconomic, cultural and political forms of rule and domination but also seeks to disclose sports’ emancipatory and subversive potential in advancing globalization from below.